The free consumption of music on streaming platforms - Novaes, Fernanda Carolina Pegoraro [UNESP]; Moreira, Walter [UNESP]; Silva, Amanda Mendes da [UNESP]; Oliveira, Alessandra Nunes de [UNESP] (Ibersid Network, 2022)
The 60's and 70's were marked by protests against the cultural industry, with music traffic through MP3. To destroy online piracy, streaming platforms have emer-ged, offering free music. With this in mind, the general objective of the present research is to reflect on how the consumption of music interferes with its own repre-sentation. To this end, the following specif-ic objectives were established: a) to gather bibliog-raphy on the theme free music ; b) investigate how information science can benefit people through the Internet of Things; c) highlight capitalism generated in the music market and the main points about streaming platforms and music sales. It is concluded that every technologi-cal performance of music is marked by the interest of the market (which has influenced and continues to in-fluence cultural choices).
Keywords: Music industry; Streaming; Music for free